Analisa Quality Of Service Menggunakan Aplikasi Gnump3d sebagai Server Media Streaming - Azhar, Raisul; Santoso, Heroe; Faisal, Faisal (Jurnal Bumigora Information Technology (BITe), 2021)
– Streaming is a term for a video or audio file that can be played without first downloading the file. Streaming can also be interpreted as a technique used to transfer data so that it can be processed continuously and continuously. Currently, there are many applications that run audio and video streaming, such as Gnump3d, Spotify, Joox, Deezer and so on. The number of applications does not guarantee the quality of service or good QoS if run on the internet network that passes through many network devices. QoS problems on Audio Streaming media will not be seen much on physical servers but will be seen if the application is installed on a Virtual Private Server. The purpose of this study is to determine the level of service quality or QoS generated by a Gnump3d application installed on a VPS by only paying attention to the parameters of Delay, Jiiter, Packet, Loss and Throughput. The research methodology uses the Network Development Life Cycle (NDLC) methodology. The results of this study obtained that the QoS of audio streaming is considered good based on the TIPHON QoS measurement standard and only one QoS parameter is considered to have failed, namely Jitter because it has a value that does not match the standard.